2017
DOI: 10.1016/j.jallcom.2016.09.169
|View full text |Cite
|
Sign up to set email alerts
|

First-order magneto-structural transition and magnetocaloric effect in Mn(Co0.96Fe0.04)Ge

Abstract: . (2017). First-order magneto-structural transition and magnetocaloric effect in Mn(Co0.96Fe0.04)Ge. Journal of Alloys and Compounds, First-order magneto-structural transition and magnetocaloric effect in Mn(Co0.96Fe0.04)Ge AbstractThe magnetic properties and magnetic structure of an as-prepared Mn(Co0.96Fe0.04)Ge sample has been investigated by powder neutron diffraction as well as X-ray diffraction and magnetisation measurements. The sample has a ferromagnetic structure in the low-temperature orthorhombic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Comparing the peak values, it is found that TbCo 2 has the largest − S max value of 6.0 J kg −1 K −1 followed by 3.2 J kg −1 K −1 , 2.83 J kg −1 K −1 , and 2.74 J kg −1 K −1 for TbCo 2 Mn 0.1 , TbCo 2 Mn 0.2 , and TbCo 2 Mn 0.3 , respectively. The differences in the magnetic entropy for these compounds reflect that the type of magnetic transition has changed from rescaled temperature ࣸ was specified as follows [18,19]:…”
Section: B Magnetic Phase Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the peak values, it is found that TbCo 2 has the largest − S max value of 6.0 J kg −1 K −1 followed by 3.2 J kg −1 K −1 , 2.83 J kg −1 K −1 , and 2.74 J kg −1 K −1 for TbCo 2 Mn 0.1 , TbCo 2 Mn 0.2 , and TbCo 2 Mn 0.3 , respectively. The differences in the magnetic entropy for these compounds reflect that the type of magnetic transition has changed from rescaled temperature ࣸ was specified as follows [18,19]:…”
Section: B Magnetic Phase Transitionmentioning
confidence: 99%
“…However, this first order magnetic phase transition for x = 0 changes to second order after the introduction of Mn. We plotted master curves of the magnetic entropy changes [18,19] to clearly identify the transformation from first order to second order, as well as detailed refinement of diffraction data near the magnetic phase transition temperature to verify the change in crystal structure. Finally, the critical behavior around T C was investigated using the Kouvel-Fisher technique to precisely analyze the nature of the second order transitions for all the TbCo 2 Mn x (x = 0.1, 0.2, and 0.3) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Although the key role of hysteresis for reversibility was well established almost one decade ago [9][10][11] , a significant number of studies on caloric effects do not address this issue yet. Promising materials have been declared without revealing the hysteresis width 6,[12][13][14] or reporting hysteresis widths that would entail manifestly excessive fields for a practical implementation 13,[15][16][17] . While these considerations do not invalidate previous works, it is undoubtedly important to have information about such features whenever possible for the purpose of practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [8] have performed a study of both Mn and Co substitution by Fe, and in spite of different chemical and physical properties of these two atoms, both magnetic and structural properties of the compounds were comparable. Ren et al [23] have reported that a 4 at.% substitution of Fe for Co in MnCoGe is sufficient to tune the magnetostructural transition at 299 K, leading to maximum magnetic entropy change (-ΔS M ) of 11 J.Kg -1 K -1 for a magnetic field change (ΔH) = 5 T. Aryal et al [24] obtained a first-order magnetostructural transition in Mn 1-…”
Section: Introductionmentioning
confidence: 99%